Shrinkage-resistant balled yarn and preparation method thereof
By using anti-shrinkage spheroidized filaments with specific ratios in the production of ductile cast iron, the problem of low pearlite content in the casting is solved, and the effect of improving the strength and hardness of the casting is achieved, while reducing the shrinkage phenomenon.
Patent Information
- Application Number
- CN202310058520.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-01-16
- Publication Date
- 2025-04-29
- Estimated Expiration
- 2043-01-16
AI Technical Summary
Although the existing spheroidized wire can improve the quality of the castings in the production of ductile iron, the pearlite content in the castings is low, resulting in insufficient strength.
An anti-shrinkage spheroidized filament is adopted, which includes a mixture of magnesium, pure lanthanum and antimony, calcium silicon, barium silicon, ferrosilicon and iron, etc., and the pearlite content of the casting is increased through specific ratios and preparation methods and reduces the shrinkage phenomenon.
By increasing the pearlite content of the casting, the strength and hardness of the casting are significantly improved, the shrinkage phenomenon is reduced, and the overall quality of the casting is improved.
Smart Images

Figure BDA0004060877150000061 
Figure BDA0004060877150000071
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of ductile iron production additives, and in particular to a shrinkage-resistant spheroidized wire and a preparation method thereof. Background Art
[0002] Shrinkage refers to the formation of scattered and tiny shrinkage cavities in the last solidified area of the casting without the shrinkage of the liquid metal or alloy. It is often scattered in the axial area of the casting wall thickness, the thick part, the root of the riser and near the inner gate. When the shrinkage porosity and the shrinkage cavity have the same volume, the distribution area of the shrinkage porosity is much larger than that of the shrinkage cavity. Shrinkage porosity is hidden inside the casting and is not easy to be found from the appearance. In the related technology, the quality of steelmaking casting products can be effectively improved by adding spheroidizing agent or spheroidizing wire.
[0003] Ordinary spheroidizers are made by melting and pouring several alloys or metals in an electric furnace into a certain shape, or crushing them into particles of a certain size. Spheroidized wire is also called spheroidized cored wire. Spheroidized cored wire is made by first crushing a certain composition of spheroidizer into powder particles of a certain fineness, and then using a wire wrapping machine to wrap the spheroidizer powder particles or several alloy powder particles into a metal wire of a certain thickness with iron sheets of a certain width and thickness. When used, a special wire feeder is used to feed the molten metal at a certain speed. When the surface of the spheroidized wire is melted, the wire core can be fully dissolved in the ideal position and produce a chemical reaction, avoiding reaction with air and slag, and changing the morphology of molten steel inclusions. The use effect is better than that of ordinary spheroidizers.
[0004] There are many types of spheroidized wires, and they are often used to produce ductile iron. In the related art, the composition and mass percentage of the core powder include: Mg: 28-32%, Si: 43-46%, Ca: 2-4%, Ba: 8-10%, and the rest is Fe and impurities; the spheroidizing agent is used in the spheroidizing step in the ductile casting production process, the amount of cementite forming elements is small, the spheroidizing quality is improved, and the feeding amount of the cored wire is saved, reducing the production cost.
[0005] However, in the application process of related spheroidized wire, although the quality of castings can be improved to a certain extent, the pearlite content in the castings is low. Pearlite is a mechanical mixture composed of ferrite and cementite, and its mechanical properties are between ferrite and cementite, that is, its strength and hardness are significantly higher than ferrite. The low content of pearlite in the casting leads to insufficient strength of the casting. Summary of the invention
[0006] In order to reduce the shrinkage phenomenon of castings and increase the pearlite content of castings, the present application provides a shrinkage-resistant spheroidized wire and a preparation method thereof.
[0007] In the first aspect, the present application provides a shrink-resistant ballized yarn, which adopts the following technical solution:
[0008] A shrink-proof ballized wire comprises the following raw materials in parts by weight: 23-27 parts of magnesium, 1.5-7 parts of a mixture of pure lanthanum and antimony, 8-12 parts of calcium silicon, 2.5-5.5 parts of barium silicon, 47-55 parts of ferrosilicon and 3-8 parts of iron.
[0009] By adopting the above technical scheme, the present application mainly increases the pearlite content of the casting and reduces the shrinkage phenomenon of the casting by selecting the raw materials and their proportions; and through the coordination between the raw materials, the technical effect is better. Among them, by mixing pure lanthanum and antimony, there is a synergistic effect between the two, which can reduce the shrinkage phenomenon of the casting, cooperate with magnesium to improve the quality of the casting, and the two work together to reduce the amount of rare earth metal used, thereby increasing the pearlite content of the casting.
[0010] Preferably, in the mixture of pure lanthanum and antimony, the weight ratio of pure lanthanum to antimony is 1:2.
[0011] By adopting the above technical solution and through practical application, this ratio is optimal.
[0012] Preferably, the shrinkage-resistant ballized yarn further comprises 0.5-2 parts by weight of nano silicon carbide.
[0013] By adopting the above technical solution, after adding nano silicon carbide, a layer of silicon dioxide is easily formed on the surface of nano SiC particles, and its presence can delay the melting reaction of SiC, thereby delaying the precipitation and retention time of carbon aggregates, and preventing excessively fast component homogenization. At the same time, the melting reaction of SiC is an endothermic process, which can reduce the diffusion rate of C and Si; therefore, silicon carbide has always been used as an inoculant, but when nano silicon carbide is applied to the spheroidizing agent, it can work together with the spheroidizing wire system to improve the spheroidizing reaction and reduce shrinkage.
[0014] Preferably, the shrinkage-resistant ballized yarn further comprises 0.1-0.5 parts by weight of a particle size regulator.
[0015] By adopting the above technical scheme and adding a particle size regulator, the particle distribution of the spheroidized wire can be made more uniform during the preparation process, so that the texture of the spheroidized wire is more uniform. By adjusting the particle size of the spheroidized wire particles, it is found that the pearlite content can be increased; and the amount of rare earth metal used can be reduced, thereby further increasing the pearlite content in the casting.
[0016] Preferably, the particle size regulator comprises the following raw materials in parts by weight: 5-7 parts of vanadium carbide, 0.1-0.3 parts of thallium carbide and 0.5-2 parts of titanium carbide.
[0017] By adopting the above technical solution, the dosage of the three raw materials in the particle size regulator can be the endpoint value within the range or any value within the range.
[0018] Preferably, the particle size regulator is added in an amount of 0.3 parts by weight.
[0019] In a second aspect, the present application provides a method for preparing shrinkage-resistant ballized yarn, which adopts the following technical solution:
[0020] A method for preparing shrinkage-resistant ballized yarn comprises the following preparation steps:
[0021] S1. Melting: weighing various raw materials by weight and mixing them at a mixing temperature of 1350-1450° C. to obtain alloy molten iron;
[0022] S2, pouring mold: pouring the alloy iron molten metal obtained in S1 into the mold and cooling it to obtain alloy iron blocks;
[0023] S3, crushing: removing the alloy iron block obtained in S2 from the mold and crushing it to obtain alloy fragments;
[0024] S4, granulation: ball-milling the alloy fragments obtained in S3 to obtain alloy particles, the particle size of which is ≤0.6 mm;
[0025] S5, powder coating: The alloy particles obtained in S4 are coated with steel sheets to obtain spheroidized wire.
[0026] By adopting the above technical solution, the preparation method of the present application has no technical difficulties and can be used in conventional factories. It is suitable for expanding production and does not require special improvements to production equipment.
[0027] As a preferred method: a method for preparing shrinkage-resistant ballized yarn comprises the following steps:
[0028] S1. Melting: weighing all raw materials except the particle size regulator according to weight, and then mixing them at a mixing temperature of 1350-1450° C. to obtain alloy molten iron;
[0029] S2, pouring mold: pouring the alloy iron molten metal obtained in S1 into the mold and cooling it to obtain alloy iron blocks;
[0030] S3, crushing: removing the alloy iron block obtained in S2 from the mold and crushing it to obtain alloy fragments;
[0031] S4, granulation: the alloy pieces obtained in S3 are mixed with a particle size regulator, and then ball-milled to obtain alloy particles, wherein the particle size of the alloy particles is ≤0.6 mm;
[0032] S5, powder coating: The alloy particles obtained in S4 are coated with steel sheets to obtain spheroidized wire.
[0033] By adopting the above technical solution, the particle size regulator can be added in the granulation step. The melting temperature of the particle size regulator is relatively high, and it is more difficult to disperse it after melting. Therefore, adding it in the granulation step has a better effect.
[0034] In summary, the present application includes at least one of the following beneficial technical effects:
[0035] 1. The present application mainly improves the pearlite content of the casting and reduces the shrinkage phenomenon of the casting by selecting raw materials and their proportions; and through the coordination between the raw materials, the technical effect is better, wherein, by mixing pure lanthanum and antimony, the two have a synergistic effect, which can reduce the shrinkage phenomenon of the casting, and cooperate with magnesium to improve the quality of the casting, and the two work together to reduce the amount of rare earth metal, thereby increasing the pearlite content of the casting; by adding a particle size regulator, the particle distribution of the spheroidized wire can be more uniform during the preparation process, so that the texture of the spheroidized wire is more uniform, and by adjusting the particle size of the spheroidized wire, it is found that it can increase the pearlite content; and the amount of rare earth metal can be reduced, thereby further increasing the pearlite content in the casting.
[0036] 2. The castings prepared by the spheroidized wire prepared in the present application have a pearlite content of 64% or more, a Brinell hardness greater than 212.3 HBW, and an impact toughness of 12.1 J / cm2 or more; this indicates that the spheroidized wire of the present application can effectively reduce the shrinkage phenomenon of the casting, increase the pearlite content gradually, and improve the quality of the casting. DETAILED DESCRIPTION
[0037] The present application is further described in detail below in conjunction with the specific contents.
[0038] raw material
[0039] The average particle size of the nano-silicon carbide used in the examples of the present application is 50 nm; the remaining raw materials are common commercial products.
[0040] Preparation Example
[0041] Preparation Example 1
[0042] A particle size regulator, the raw materials and the amounts of the raw materials are shown in Table 1, and the preparation method is as follows:
[0043] Weigh 6 kg of vanadium carbide, 0.2 kg of thallium carbide and 1 kg of titanium carbide, and then mix them to obtain a particle size regulator.
[0044] Example
[0045] Examples 1-3
[0046] A kind of shrinkage-resistant ballized yarn, the raw materials and the amount of each raw material are shown in Table 1, and the preparation method is as follows:
[0047] S1. Melting: weighing various raw materials by weight and mixing them at a mixing temperature of 1400° C. to obtain alloy molten iron;
[0048] S2, pouring mold: pouring the alloy iron molten metal obtained in S1 into the mold and cooling it to obtain alloy iron blocks;
[0049] S3, crushing: removing the alloy iron block obtained in S2 from the mold and crushing it to obtain alloy fragments;
[0050] S4, granulation: ball-milling the alloy fragments obtained in S3 to obtain alloy particles, wherein the particle size of the alloy particles is ≤0.6 mm;
[0051] S5, powder coating: The alloy particles obtained in S4 are coated with steel sheets to obtain spheroidized wire.
[0052] Wherein, in the mixture of pure lanthanum and antimony, the weight ratio of pure lanthanum to antimony is 1:2.
[0053] Table 1 Raw materials and amounts of raw materials in Examples 1-3 (kg)
[0054] Example 1 Example 2 Example 3 magnesium 23 25 27 A mixture of pure lanthanum and antimony 7 7 7 Calcium Silicon 8 10 12 Silicon Barium 5.5 4 2.5 Ferrosilicon 47 51 55 iron 8 5 3
[0055] Example 4
[0056] A shrinkage-resistant ballized yarn, which is different from Example 2 in that its raw materials also include 1 kg of nano-silicon carbide, and the remaining steps are the same as Example 2.
[0057] Example 5
[0058] A shrinkage-resistant balled yarn, which is different from Example 4 in that its raw materials further include 0.1 kg of a particle size regulator, and the particle size regulator comes from Preparation Example 1. The preparation steps of the shrinkage-resistant balled yarn are as follows:
[0059] S1. Melting: weighing all raw materials except the particle size regulator according to weight, and then mixing them at a mixing temperature of 1350-1450° C. to obtain alloy molten iron;
[0060] S2, pouring mold: pouring the alloy iron molten metal obtained in S1 into the mold and cooling it to obtain alloy iron blocks;
[0061] S3, crushing: removing the alloy iron block obtained in S2 from the mold and crushing it to obtain alloy fragments;
[0062] S4, granulation: the alloy pieces obtained in S3 are mixed with a particle size regulator, and then ball-milled to obtain alloy particles, wherein the particle size of the alloy particles is ≤0.6 mm;
[0063] S5, powder coating: The alloy particles obtained in S4 are coated with steel sheets to obtain spheroidized wire.
[0064] Example 6
[0065] A shrink-proof balled yarn, which is different from Example 5 in that the amount of particle size regulator added is 0.3 kg, and the remaining steps are the same as Example 5.
[0066] Example 7
[0067] A shrink-proof balled yarn, which is different from Example 5 in that the amount of particle size regulator added is 0.5 kg, and the remaining steps are the same as Example 5.
[0068] Example 8
[0069] A shrinkage-resistant spheronized wire, which is different from Example 6 in that the added amount of the mixture of pure lanthanum and antimony is 5 kg, and the remaining steps are the same as Example 6.
[0070] Example 9
[0071] A shrinkage-resistant spheronized wire, which is different from Example 6 in that the added amount of the mixture of pure lanthanum and antimony is 3 kg, and the remaining steps are the same as those of Example 6.
[0072] Example 10
[0073] A shrinkage-resistant spheronized wire, which is different from Example 6 in that the added amount of the mixture of pure lanthanum and antimony is 1.5 kg, and the remaining steps are the same as those of Example 6.
[0074] Embodiment 11
[0075] A shrinkage-resistant ballized yarn, which is different from Example 5 in that thallium carbide is not added to the raw materials of its particle size regulator, and the remaining steps are the same as those of Example 5.
[0076] Example 12
[0077] A shrinkage-resistant ballized yarn, which is different from Example 5 in that titanium carbide is not added to the raw materials of its particle size regulator, and the remaining steps are the same as Example 5.
[0078] Comparative Example
[0079] Comparative Example 1
[0080] A shrinkage-resistant spheronized wire, which is different from Example 1 in that the mixture of pure lanthanum and antimony is replaced by an equal amount of pure lanthanum, and the remaining steps are the same as those of Example 1.
[0081] Comparative Example 2
[0082] A shrinkage-resistant spheronized wire, which is different from Example 1 in that the mixture of pure lanthanum and antimony is replaced by an equal amount of antimony, and the remaining steps are the same as those of Example 1.
[0083] Performance testing
[0084] Detection method / test method
[0085] Shrinkage-resistant spheroidized yarns were prepared according to the preparation methods of Examples 1-12 and Comparative Examples 1-2, respectively. Then, the properties of the spheroidized yarns were tested according to the following tests. The test results are shown in Table 2.
[0086] 1. Test plan:
[0087] 1) In the same furnace of molten iron, the spheroidizing wire is replaced in different packages;
[0088] 2) Experimental process: molten iron treatment process: melt the molten iron in a hot blast cupola, desulfurize in front of the furnace, and use a medium frequency furnace; then add 3-7mm silicon particles to adjust the silicon content according to the original molten iron composition before spheroidization, and add silicon-barium-calcium inoculant with a particle size of 1-4mm in the casting ladle, add spheroidizing wire with a mass fraction of 0.4% for wire feeding treatment of 0.5t molten iron / time, the height-to-diameter ratio of the molten iron in the treatment ladle is =1.4:1, the spheroidizing treatment temperature is ≥1520℃, boxless vertical molding, transfer ladle casting, and the pouring time is 5-7min.
[0089] Chemical composition of raw iron (mass fraction, %)
[0090] C Mn Si S P Ce 3.5 0.12 1.6 0.021 0.05 2.2
[0091] 2. Hardness: The hardness of castings made of spheroidized wire is tested according to the national standard GB / T 231.1-2018 "Brinell hardness test for metal materials". The testing environment is: 23℃.
[0092] 3. Impact toughness: The hardness of castings made of spheroidized wire is tested according to the national standard GB / T 1817-2017 "Test method for room temperature impact toughness of cemented carbide". The testing environment is: 23℃.
[0093] Table 2 Test data of Examples 1-12 and Comparative Examples 1-2
[0094]
[0095]
[0096] It can be seen from Examples 1-12 and Comparative Examples 1-2, as well as the test data in Table 2, that the castings prepared by the spheroidized wire prepared in the present application have a pearlite content of 64% or more, and a Brinell hardness greater than 212.3 HBW, and an impact toughness of 12.1 J / cm2 or more; this indicates that the spheroidized wire of the present application can effectively reduce the shrinkage phenomenon of the casting, increase the pearlite content gradually, and improve the quality of the casting.
[0097] It can be seen from the test data of Examples 1-3 that the ratio of each raw material in Example 2 of the present application is better. And combined with Comparative Examples 1-2, the present application can use the synergistic effect of pure lanthanum and antimony to increase the pearlite content of the casting by mixing them. Combined with Example 4, after the raw materials are added with nano-silicon carbide, a layer of silicon dioxide is easily formed on the surface of the nano-SiC particles. Its presence can delay the melting reaction of SiC, thereby delaying the precipitation and retention time of carbon aggregates, and preventing excessively fast component homogenization. At the same time, the melting reaction of SiC is an endothermic process, which can reduce the diffusion rate of C and Si; therefore, silicon carbide has always been used as an inoculant, but nano-silicon carbide is applied to the spheroidizing agent, which can work together with the spheroidizing wire system to improve the spheroidizing reaction and reduce shrinkage.
[0098] Through Examples 5-7, it can be seen that by adding a particle size regulator, the particle distribution of the spheroidized silk can be made more uniform during the preparation process, so that the texture of the spheroidized silk can be made more uniform. By adjusting the particle size of the spheroidized silk, it is found that the content of pearlite can be increased. In combination with Examples 8-10, when the addition amount of the mixture of pure lanthanum and antimony is reduced, it is helpful to increase the content of pearlite. By adding a particle size regulator, the content of pearlite can be increased while ensuring the hardness and impact toughness of the casting; and through experiments, the optimal addition amount of the mixture of pure lanthanum and antimony is 3kg.
[0099] It can be seen from the test data of Example 5 and Examples 11-12 that there is a synergistic effect between thallium carbide, titanium carbide and vanadium carbide in the particle size regulator of the present application.
[0100] The above-mentioned specific implementation examples are all preferred embodiments of the present application, and are not intended to limit the protection scope of the present application. Therefore, all equivalent changes made based on the structure, shape, and principle of the present application should be included in the protection scope of the present application.
Claims
1. A shrink-resistant ballized yarn, characterized in that: The method comprises the following raw materials in parts by weight: 23-27 parts of magnesium, 1.5-7 parts of a mixture of pure lanthanum and antimony, 8-12 parts of calcium silicon, 2.5-5.5 parts of barium silicon, 47-55 parts of ferrosilicon and 3-8 parts of iron; The shrink-resistant ballized yarn also includes 0.5-2 parts by weight of nano silicon carbide; The shrink-resistant ballized yarn further comprises 0.1-0.5 parts by weight of a particle size regulator; The particle size regulator comprises the following raw materials in parts by weight: 5-7 parts of vanadium carbide, 0.1-0.3 parts of thallium carbide and 0.5-2 parts of titanium carbide.
2. The shrink-resistant ballized yarn according to claim 1, characterized in that: In the mixture of pure lanthanum and antimony, the weight ratio of pure lanthanum to antimony is 1:
2.
3. The shrink-resistant ballized yarn according to claim 1, characterized in that: The added amount of the particle size regulator is 0.3 parts by weight.
4. A method for preparing a shrinkage-resistant ballized yarn according to any one of claims 1 to 3, characterized in that: It includes the following steps: S1. Melting: weighing all raw materials except the particle size regulator according to weight, and then mixing them at a mixing temperature of 1350-1450° C. to obtain alloy molten iron; S2, pouring mold: pouring the alloy iron molten metal obtained in S1 into the mold and cooling it to obtain alloy iron blocks; S3, crushing: removing the alloy iron block obtained in S2 from the mold and crushing it to obtain alloy fragments; S4, granulation: the alloy pieces obtained in S3 are mixed with a particle size regulator, and then ball-milled to obtain alloy particles, wherein the particle size of the alloy particles is ≤0.6 mm; S5, powder coating: The alloy particles obtained in S4 are coated with steel sheets to obtain spheroidized wire.
Citation Information
Patent Citations
Spheroidizing agent special for wind power generation equipment casting
CN109762955A
Cladding nodulizer for high strength nodular cast iron alloy
CN1280205A